(untitled) (Mustansiria Dental Journal, 2018)
Preoperative prophylactic protocol in oral surgery is well established practice; still it’s not used in Iraqi surgical centers. The aim of this study is to show that preoperative protocol is reliable surgical practice. 58 patients, selected from the attendant of oral surgery clinic in Alkarama specialized dentistry center/Baghdad, were subjected to various oral surgical procedures 59 operations under local anesthesia. These patient were given single dose antibiotic prophylaxis preoperatively after we divide them into 3 groups, 1st group were given 1 gm amoxicillin (control group),second group were given 1 million i.u. of procaine penicillin; 3rd group were given 500 mg ampicillin vial,. The maximum time for all procedures was 2 hours. We concluded that preoperative antibiotic prophylaxis can be used safely in out patient’s oral surgical procedures, on Iraqi patient with minimum complications.